Analisis Redesain Fasilitas Produksi Departemen Pewarnaan Guna Meminimalisir Biaya Material Handling pada PT. Surya Pertiwi Nusantara - Bagus, Arnoldus Ivan; Purnama, Jaka (SURYA TEKNIKA, 2025)
Factory layout is a facility design that aims to facilitate efficient material movement and optimal utilisation of production areas. PT. Surya Pertiwi Nusantara is a company engaged in the manufacture of sanitary ware. Based on observations in the colouring department, there are problems with the material transfer process, namely the distance between work stations is quite far, which has an impact on travel time. This results in wasteful material handling costs. Data processing was carried out using the From To Chart method and Activity Relationship Chart. The results of the research using the From To Chart method produced an alternative layout with a material handling moment of 7,814. 342.8 metres/month and OMH of Rp. 940,846,873.1/month, compared to the initial layout, which had a material handling moment of 18,334,175.2 metres/month and OMH of Rp. 1,078,049,501.8/month. Based on these results, the layout alternative using the From To Chart method was chosen.